Laboratory investigation of the spatial thermodynamic properties of the bridge approach in the permafrost region - Yin, Qixiang; Wu, Junjie; Zhang, Boyang; Hou, Mingjiao (Frontiers in Earth Science, 2024)
As the highest altitude and the longest plateau railway line, the Qinghai–Tibet railway passes through a large area of continuous permafrost. As the key position of the combination of roadbed and bridge, the stability and strength of the bridge approach directly affect the smoothness of the whole line. Through an indoor model test, the distribution pattern of space temperature field and the change law of temperature measuring points in the bridge approach of gravel sandwich are studied. With the increase in the depth from the subgrade surface, the influence of the temperature change in the upper atmosphere decreases gradually at the 2.5-m platform back of the subgrade center section, resulting in an obvious lag in the subgrade. By comparing the temperature measurement data of different bridge approaches of the gravel interlayer road bridge and the bridge approach of the U-shaped block gravel road bridge, it is shown that the U-shaped structure not only has a better overall cooling effect, but also the cooling effect gradually increases with the increase in the distance from the abutment back. The influence range of the road–bridge transition section on the spatial temperature field is approximately 14 m in the back of the abutment, and the influence range at 7.5 m is the most severe. The research results have important practical significance and engineering application value for the operation and maintenance of the Qinghai–Tibet railway.